The assessment of intersegmental motion and pelvic tilt in elite oarsmen - McGregor, A.; Anderton, L.; Gedroyc, W. (Medicine & Science in Sports & Exercise, 2002)
Low back pain (LBP) is a common problem in elite oarsmen. The relevance of spinal and pelvic flexibility to good rowing technique and the incidence of LBP is unclear. PURPOSE: The aim of this study was to investigate patterns of spinal and pelvic mobility in a group of elite oarsmen with and without a history of LBP. METHODS: Twenty elite oarsmen were recruited into this study, including nine with no history of spinal problems, four with a current spinal problem, and the remainder with a history of LBP. Subjects were scanned using an interventional magnetic resonance imaging (MRI) scanner. Four key stages of the rowing stroke were simulated within the scanner, and sagittal images of the lumbar spine and sacrum were obtained. From these images intersegmental motion was determined along with the angle of lordosis and position of the lumbar spine and sacrum. RESULTS: Different mobility trends were seen; oarsmen with no history of LBP demonstrated the greatest mobility in their lower lumbar regions (at the L5/S1 level in the catch position 7.5 degrees +/-1.3 in normals; 4.8 degrees +/-1.2 in previous LBP groups; and 2.8 degrees +/-5.5 in current LBP group) and the lowest rotation of their pelvis (level in the catch position 13.9 degrees +/-11.2 in normals; 16.1 degrees +/-6.8 in previous back pain groups; and 15.2 degrees +/-11.2 in current back pain group). In contrast, those with either current or previous LBP presented with a hypomobility of their spine which appeared to be compensated for by increased pelvic rotation. CONCLUSIONS: Marked differences were observed in the motion characteristics of these 3 groups of oarsmen. At present it is not known if these changes are causative or effect.